Application of HEC-RAS for the Study of Sediment Continuity in the Clain River (Poitiers, France) - Ghzayel, Alaa; Beaudoin, Anthony (Journal of Hydrological Ecology and Water Security, 2025)
Research on sediment transport has focused on large dams, whose impacts are more visibly dramatic. The impacts of low-head dams, which are smaller and more numerous, have received less attention. It is partly due to the challenges of modeling sediment transport in these environments, which requires high-resolution data on flow dynamics and sediment properties. This work shows that there are tools allowing the acquisition of these hydrometric data and that the hydro-morphodynamic models can integrate it. The study site is the Clain river flowing through the Grand Poitiers municipality in the Vienne department (France), where low-head dams are installed at two key sites, Îlot Tison and Saint-Benoît, which pose potential barriers to sediment continuity. The hydro-morphodynamics of the Clain river are studied by means of the software HEC-RAS. The numerical simulations, performed in this work, show that the software HEC-RAS uses water flow and sediment transport equations tailored to specific conditions of the Clain river, a plain river with low-head dams. The robustness of the turbulent model and sediment transport laws present in the software HEC-RAS was checked for this river type. These numerical simulations allowed us to elucidate the hydro-morphodynamic impacts of two low-head dams present at the Saint-Benoît and Îlot Tison sites, on the Grand Poitiers municipality. For specific discharges exceeding the mean specific discharge of the Clain river, the low-head dams are bypassed. For specific discharges below the mean specific discharge of the Clain river, disturbances in water flow and sediment transport occur locally around these low-head dams. The occurrence of two phenomena, erosional narrowing and widening, depends on the height of the removal dam, the specific discharge, and the volume of stored sediments upstream of the removal dam. Removing these two low-head dams doesn’t disturb the hydro-morphodynamics of the Clain river at the large scale.